On the activation strategy of the chiller in water-loop self-contained refrigeration systems: An experimental analysis. (September 2015) - Bagarella, G.; Lazzarin, R.; Noro, M.
Abstract: Supermarkets require considerable amount of electricity and gas for refrigeration and maintenance of comfortable retail environment conditions. They are also responsible for a large amount of both direct and indirect CO2 emissions. Nowadays advanced refrigeration systems for supermarkets can reduce both annual energy consumption and total equivalent warming impact. One of these advanced solutions is the water-loop self-contained refrigeration system, where the thermal power of each cabinet is rejected to a fluid-loop, refrigerated either by a dry-cooler or by a central chiller. In this study the performances of a real water-loop self-contained plant are analyzed to establish whether the activation of the water-loop chiller is energy effective or not varying the external air temperature. The activation strategy of the chiller is a crucial issue, which dramatically affects the energy performances of the whole system. Highlights: The WLSC system is a kind of advanced refrigeration plant for supermarkets. The performances of a real WLSC plant are analyzed varying the external air temperature. The scope is to establish if the activation of the water-loop chiller is energy effective. In the system control the water-loop chiller activation strategy is a crucial element.